2009
DOI: 10.1111/j.1398-9995.2009.02054.x
|View full text |Cite
|
Sign up to set email alerts
|

Low‐dose cyclosporine A therapy increases the regulatory T cell population in patients with atopic dermatitis

Abstract: Our results indicate that the therapeutic effect of low-dose CsA therapy in AD patients might be not only mediated by the inhibition of T cell hyperactivity but also by an increased population of Treg cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(70 citation statements)
references
References 40 publications
3
64
0
2
Order By: Relevance
“…Although in the past decade, further T-cell populations, in particular regulatory T-cells [35,36] were described to be involved in the regulation of allergic inflammation, the protective role of IFN-γ in atopy is still accepted. Data from animal studies clearly demonstrate that the asthma-protective effect induced by microbial exposure depends on IFN-γ [37,38]. In our study, we demonstrate that sleeping on animal fur in the first 3 months of life contributes to persistently higher amounts of IFN-γ-producing peripheral T-cells at least until the age of 3 years in a subgroup of the study population.…”
Section: Discussionsupporting
confidence: 48%
“…Although in the past decade, further T-cell populations, in particular regulatory T-cells [35,36] were described to be involved in the regulation of allergic inflammation, the protective role of IFN-γ in atopy is still accepted. Data from animal studies clearly demonstrate that the asthma-protective effect induced by microbial exposure depends on IFN-γ [37,38]. In our study, we demonstrate that sleeping on animal fur in the first 3 months of life contributes to persistently higher amounts of IFN-γ-producing peripheral T-cells at least until the age of 3 years in a subgroup of the study population.…”
Section: Discussionsupporting
confidence: 48%
“…Additional studies are needed for the evaluation and establishment of an individualized CsA/FK506 therapy. Individualized immunosuppressive regimes are gaining importance by new concepts of CsA tapering in renal transplant patients (16) and low-dose CsA therapies in atopic dermatitis patients (51).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been shown that the effect of CsA on Treg depends on its concentration. Low CsA concentrations allow Treg expansion, whereas high concentrations lead to a decreased Treg number (17,32,33). This phenomenon can be explained through interleukin-2 (IL-2) action.…”
Section: Application To New Patientsmentioning
confidence: 99%